2007
DOI: 10.2139/ssrn.1024090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grade Retention on Child Test Scores

Abstract: Each year an estimated two million children in the United States repeat a grade. Investing an additional year in the same grade is expected to help a child to acquire the academic skills she lacks. This, in turn, would help her to be successful in higher grades. In spite of its popularity, grade retention remains a highly controversial practice. A majority of researchers find that, for the repeaters, repeating a grade is strongly correlated with the poor performance in mathematics and reading tests. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…2), which were again screened by the first two authors independently. Finally, 84 studies (Afsa, 2011;Alet, Bonnal, & Favard, 2013;Allensworth, 2005;André, 2009;Andrew, 2014;Appelmans, 2016;Battistin & Schizzerotto, 2012Belot & Vandenberghe, 2014;Bhattacharya, 2008;Bietenbeck, 2014 Jacob & Lefgren, 2004, 2009Keslair, 2007;Klapproth et al, 2016;Koppensteiner, 2014 Hughes, 2012;Nunes, Balcão Reis, & Seabra, 2018;Okurut, 2018;Ou & Reynolds, 2010;Ozek, 2015;Park, Steiner, & Kaplan, 2018;Pereira & Reis, 2014;Peterson & Hughes, 2011;Roderick & Nagaoka, 2005;Schumann, 2012;Schwerdt et al, 2017;Troncin, 2005;Uysal, 2010;Vandecandelaere, Schmitt, Vanlaar, De Fraine, & Van Damme, 2016c;Vandecandelaere, Vanlaar, Goos, De Fraine, & Van Damme, 2011, 2013Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2016a, 2016bWinters & Greene, 2012;Wu, West, & Hughes, 2008 covering 1328 single effects were included in our review (see Fig. 2).…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2), which were again screened by the first two authors independently. Finally, 84 studies (Afsa, 2011;Alet, Bonnal, & Favard, 2013;Allensworth, 2005;André, 2009;Andrew, 2014;Appelmans, 2016;Battistin & Schizzerotto, 2012Belot & Vandenberghe, 2014;Bhattacharya, 2008;Bietenbeck, 2014 Jacob & Lefgren, 2004, 2009Keslair, 2007;Klapproth et al, 2016;Koppensteiner, 2014 Hughes, 2012;Nunes, Balcão Reis, & Seabra, 2018;Okurut, 2018;Ou & Reynolds, 2010;Ozek, 2015;Park, Steiner, & Kaplan, 2018;Pereira & Reis, 2014;Peterson & Hughes, 2011;Roderick & Nagaoka, 2005;Schumann, 2012;Schwerdt et al, 2017;Troncin, 2005;Uysal, 2010;Vandecandelaere, Schmitt, Vanlaar, De Fraine, & Van Damme, 2016c;Vandecandelaere, Vanlaar, Goos, De Fraine, & Van Damme, 2011, 2013Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2016a, 2016bWinters & Greene, 2012;Wu, West, & Hughes, 2008 covering 1328 single effects were included in our review (see Fig. 2).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…;Cham, Hughes, West, & Im, M. H., 2015;Chen, Liu, Zhang, Shi, & Rozelle, 2010;Cockx, Picchio, & Baert, 2019;Cooley-Fruehwirth, Navarro, & Takahashi, 2016;Detienne, 2017;d' Haultfoeuille, 2010;Diris, 2012Diris, , 2017Dong, 2010;Ehmke, Drechsel, & Carstensen, 2010, 2013; Ehmke, Salzer, Pietsch, Drechsel, & Muller, 2017; Eide & Showalter, 2001; Eren, Depew, & Barnes, 2017; Ferreira Sequeda, Golsteyn, & Parra-Cely, 2018; Garcia-Perez, Hidalgo-Hidalgo, & Robles-Zurita, 2014; Gary-Bobo, Gousse, & Robin, 2016; Geng & Rockoff, 2017; Glick & Sahn, 2010; Goos, Van Damme, Onghena, &Petry, 2011;Goos, Van Damme, et al, 2013;Greene & Winters, 2007, 2009Hamlin, 2013;Hill, Weiss, & Zhai, 2011;Hofer, Farran, Lipsey, Aydogan, & Bilbrey, 2010;Hong & Raudenbush, 2005, 2006Hong & Yu, 2007, 2008Hughes, Cao, West, Smith, & Cerda, 2017;Hughes, Chen, Thoemmes, & Kwok, 2010;Hughes, West, Kim, & Bauer, 2017;Hwang & Cappella, 2018;Im, Hughes, Kwok, Puckett, & Cerda, 2013; …”
mentioning
confidence: 99%
“…Primary school. Bhattacharya, S. (2007) in The results indicate that potential grade retention, even at fourth grade, increases the propensity that a student drops out of school at a later point in time.…”
Section: Longitudinal Databasesmentioning
confidence: 85%
“…Using a DiD approach, Bhattacharya (2007) found that repetition did not add any value. Children who repeated a grade were more likely to experience a decrease in test scores than they would have if they had not been retained.…”
Section: Grade Retention and Student Outcomesmentioning
confidence: 99%